The imprinted Phlda2 gene modulates a major endocrine compartment of the placenta to regulate placental demands for maternal resources - Tunster, S.J. (Elsevier, 2016)
Imprinted genes, which are expressed from a single parental allele in response to epigenetic marks first established in the germline, function in a myriad of processes to regulate mammalian development. Recent work suggests that imprinted genes may regulate the signalling function of the placenta by modulating the size of the endocrine compartment. Here we provide in vivo evidence that this hypothesis is well founded. Elevated expression of the imprinted Pleckstrin homology-like domain, family a, member 2 (Phlda2) gene drives a reduction of the spongiotrophoblast endocrine compartment, diminished placental glycogen and asymmetric foetal growth restriction. Using both loss-of-function and gain-in-expression mouse models, here we further show that Phlda2 exclusively modulates the spongiotrophoblast compartment of the placenta without significantly altering the composition of the trophoblast giant cell endocrine lineages that share a common progenitor with this lineage. Additionally, we show that Phlda2 loss-of-function placentae contain nearly three times more placental glycogen than non-transgenic placentae. Remarkably, relative to a fully wild type scenario, wild type placentae also accumulate excessive glycogen. While loss-of-function of Phlda2 increased both placental weight and placental glycogen, the weight of both mutant and non-transgenic fetuses was lower than that found in a fully wild type scenario indicating that excessive glycogen accumulation comes at the cost of foetal growth. This work firstly highlights a novel signalling function for the spongiotrophoblast in stimulating the global accumulation of placental glycogen. Furthermore, this work suggests that Phlda2 manipulates the placenta's demands for maternal resources, a process that must be tightly regulated by epigenetic marks to ensure optimal foetal growth.